Valine in diets for Nile tilapia (Revista Ciência Agronômica, 2018)
This study verified the effect of valine on the zootechnical performance, percentage composition and growthof skeletal muscle fibre in fingerlings of Nile tilapia. A total of 270 fish (average initial weight 1.57 ± 0.05 g and total initiallength 4.16 ± 0.46 cm) were used, distributed in 18 tanks (250 litres), in a completely randomised design with six treatmentsand three replications. Six diets (26.81% DP and 3200.00 kcal DE) were formulated with increasing levels of valine (0.82, 0.86,0.98, 1.04, 1.10 and 1.26% of the diet). The zootechnical performance, percentage composition of the fish, and muscle-fibredistribution were evaluated. There was no effect from the different levels of valine (P>0.05) on zootechnical performance,percentage composition or the frequency distribution of muscle fibre. The addition of 0.82% valine (2.65% crude proteinvaline) is recommended in the diet of Nile tilapia fingerlings.